A newly proposed IVCVR controlled IUPQC device for PQ enhancement in multi-feeder distribution networks - CH. V. Ramachandra Rao; M. Arun; B. Suresh Babu (Institute of Advanced Engineering and Science, 2026)
Nowadays, the greater relevance of power-quality has being received substantial attention in multi-feeder distribution system due to increased usage of critical non-linear power-electronic loads in many applications. These loads proliferates the quality-power and it can degrade the voltage and current quality in multi-feeder networks from the utility-grid code specifications. Numerous custom-power compensation devices are accessible to mitigate corresponding voltage/current relevant PQ concerns, resulting that the multi-feeder networks are maintained as fundamentally strong, sinusoidal wave-shape, essentially balanced, linear/stable in nature. Amid of several custom-power compensation devices, the interline-UPQC is the most significant for enhancing both voltage/current waveforms in utility-grid integrated multi-feeder distribution system by employing suitable control algorithms. It is noted that, the newly proposed Integrated Voltage-Current Vector Reference (IVCVR) control algorithm eliminates the various technical issues in conventional schemes. In this work, a novel IVCVR algorithm controlled IUPQC device has been proposed for PQ enhancement and also maintaining flexible power-flow between the multi-feeders. The operation and performance of newly proposed IVCVR algorithm controlled IUPQC device has been investigated under definite PQ problems by using Matlab/Simulink software-computing tool. The extracted simulation results are highlighted with feasible interpretations complying with IEEE-519/2022 standards.